INDONESIA’S DIPLOMACY MANAGEMENT IN DEFENDING PAPUA AS PART OF NKRI - Zulham, Muhammad (Journal of Social Political Sciences, 2025)
The Papua conflict, marked by separatist claims and allegations of human rights violations, has positioned Indonesia under sustained international scrutiny. This study examines the diplomatic strategies employed by the Indonesian government to defend its sovereignty over Papua from 2020 to 2024, focusing on responses to global pressures and domestic legitimacy challenges. Grounded in neorealism and state sovereignty frameworks, the research adopts a qualitative descriptive approach to analyze Indonesia’s multi-level diplomacy involving state and non-state actors. Findings reveal a dual-track strategy: Government-to-Government (G2G) efforts prioritize bilateral engagements with influential states to counter separatist narratives, while People-to-People (P2P) initiatives focus on fostering Papuan trust in Indonesian nationalism through dialogue and grassroots empowerment. Key tactics include leveraging ASEAN partnerships to mitigate external criticism and deploying cultural diplomacy to reinforce national unity. However, challenges persist, such as balancing human rights accountability with sovereignty defense and addressing digital misinformation campaigns. This study underscores the necessity of integrating soft power and institutional legitimacy to fortify Indonesia’s diplomatic posture. Recommendations include enhancing multilateral collaboration, institutionalizing P2P programs, and adopting data-driven communication strategies to preempt disinformation. The findings offer actionable insights for policymakers to harmonize sovereignty preservation with inclusive governance in conflict-sensitive regions.